Dissociation between amygdala and bed nucleus of the stria terminalis during threat anticipation in female post‐traumatic stress disorder patients. Issue 4 (10th January 2017) - Brinkmann, Leonie; Buff, Christine; Neumeister, Paula; Tupak, Sara V.; Becker, Michael P.I.; Herrmann, Martin J.; Straube, Thomas
Abstract: Feelings of uncontrollability and anxiety regarding possibly harmful events are key features of post‐traumatic stress disorder (PTSD) symptomatology. Due to a lack of studies, the neural correlates of anticipatory anxiety in PTSD are still poorly understood. During functional magnetic resonance imaging, female PTSD patients with interpersonal violence trauma and healthy controls (HC) anticipated the temporally unpredictable presentation of aversive (human scream) or neutral sounds. Based on separate analysis models, we investigated phasic and sustained brain activations. PTSD patients reported increased anxiety during anticipation of aversive versus neutral sounds. Furthermore, we found both increased initial, phasic amygdala activation and increased sustained activation of the bed nucleus of the stria terminalis (BNST) during anticipation of aversive versus neutral sounds in PTSD patients in comparison to HC. PTSD patients as compared with HC also showed increased phasic responses in mid‐cingulate cortex (MCC), posterior cingulate cortex (PCC), mid‐insula and lateral prefrontal cortex (PFC) as well as increased sustained responses in MCC, PCC, anterior insula and lateral and medial PFC. Our results demonstrate a relationship between anticipatory anxiety in PTSD patients and hyperresponsiveness of brain regions that have previously been associated with PTSD symptomatology. Additionally, the dissociation between amygdala and BNST indicates distinct temporal and functional characteristics and suggests that phasic fear and sustained anxiety responses are enhanced during unpredictable anticipation of aversive stimuli in PTSD. Hum Brain Mapp 38:2190–2205, 2017 . ©2017 Wiley Periodicals, Inc.